1997
DOI: 10.1046/j.1365-2427.1997.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, discharge‐driven patterns of mayfly assemblages in an intermittent Neotropical stream

Abstract: 1. Streams in the seasonal wet and dry tropics have highly dynamic discharge regimes. Our study stream, located in mid‐western Brazil, drains into the Pantanal, South America’s largest wetlands, and is characterized by frequent spates in the rainy season and several weeks of interrupted flow in the dry season. 2. In order to understand how these seasonal flow patterns influence the aquatic fauna, floating litter was studied because: (i) this habitat is exposed to the current, and thus is likely to be most affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
1
12
0
10
Order By: Relevance
“…and Farrodes sp. Nolte et al (1997), in studies conducted in the Benedict River, reported the occurrence of Caenidae family after a disrupting of water flow. The food resources are another important factor determining the abundance of Caenis sp.…”
Section: Discussionmentioning
confidence: 99%
“…and Farrodes sp. Nolte et al (1997), in studies conducted in the Benedict River, reported the occurrence of Caenidae family after a disrupting of water flow. The food resources are another important factor determining the abundance of Caenis sp.…”
Section: Discussionmentioning
confidence: 99%
“…climatic stresses, habitat stability, predation and competition). Depending on the environment, a focus on response to the seasons throughout the year (see Musolin & Saulich, 1999 for an example of this approach), on seasonal stream discharge (Nolte et al, 1997) or on tidal patterns (Saigusa & Akiyama, 1995) may be appropriate. Some habitats are non-seasonal, because conditions are similar throughout the year except for unpredictable changes (Towns, 1981;Yule & Pearson, 1996).…”
Section: Environmental Differencesmentioning
confidence: 99%
“…Intermittent streams are inherently variable, with flows typically changing rapidly in response to rain events (Nolte et al, 1997), and can therefore be difficult to adequately characterize. Perennial streams have historically received greater attention than intermittent streams (Boulton and Suter, 1986;Williams, 1988), although recently more attention has been given to the importance of meteorological, geological, and land-cover controls on flows in intermittent streams (Costigan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this previous research, it is clear that our understanding of the hydrological processes controlling flow permanence and interactions between streamflow and aquifer recharge in intermittent river systems needs further improvement (Costigan et al, 2015). This knowledge gap is even more significant for tropical regions, where climate patterns are typically highly dynamic with distinct wet and dry seasons which strongly influence both surface flows and groundwater levels (Costigan et al, 2015;Nolte et al, 1997). The lack of information on intermittent stream dynamics is acute in these tropical areas, as rainfall data is missing or does not capture the high spatial variability because many catchments are ungauged, and no long-term hydrological datasets are available (Klemes, 1993).…”
Section: Introductionmentioning
confidence: 99%